Knowledge and practices related to antibiotics among poultry producers and veterinarians in two Indian states - Sharma, Garima; Dey, Tushar; Hazarika, R.A.; Shome, B.R.; Shome, R.; Singh, V.P.; Deka, Ram P.; Grace, Delia; Lindahl, Johanna F. (Elsevier, 2024)
Background Antibiotics are frequently utilized in livestock, particularly poultry, for therapy and growth promotion, resulting in antimicrobial resistance. Multidrug-resistant bacteria are frequent in poultry samples from India. The purpose of this study was to better understand main antibiotic consumption patterns in poultry value chains, as well as antibiotic knowledge and practices among the stakeholders.